Particle t'a in Snowdrift Chipewyan ... - Jehn, Richard Douglas (University of Calgary, 1980)
Some problem has arisen in accurately characterizing the general nature, the morphosyntactic description, and, in particular, the function of the putative relative clause marking particle t'a in Chipewyan. This paper attempts to provide a preliminary account of t'a. expanding on work which has preceded. ...